Bismuth-Mediated Organic Reactions - Ollevier, Thierry; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
See Table of Contents (PMP)
Keywords: Chemistry; Chemistry, Organic; Catalysis; Chemistry; Organic Chemistry; Organometallic Chemistry; Catalysis